Intertextual Analysis of Ayu Utami’s Cerita Cinta Enrico, Indonesian Legend Sangkuriang (Tangkuban Perahu), and Greek Mythology Oedipus - Septiani, Resty Maudina; Handayani, Rika (Andalas International Journal of Socio-Humanities, 2024)
This article is designed to offer comprehensive analyses of characterizations, plot, setting, intertextual relationships, and hypogram of Cerita Cinta Enrico, the folklore of Sangkuriang (Tangkuban Perahu), and the myth of Oedipus. Qualitative descriptive method is used along with intertextual approach. Based on the analysis of the data, the results are: (1) the three stories analyzed employ the main character as their title; (2) the three of them use the traditional plot and flashback; (3) all of them address Oedipus complex issue; (4) Sangkuriang (Tangkuban Perahu) and Oedipus are the hypograms of Cerita Cinta Enrico.